2009
DOI: 10.1111/j.1467-9280.2009.02310.x
|View full text |Cite
|
Sign up to set email alerts
|

Transformation Direction Influences Shape-Similarity Judgments

Abstract: Three experiments provide evidence that the perceived similarity between two images is systematically affected by the inherent direction of a transformation that links the two. Participants were shown short animations morphing one object into another from the same basic category. They were then asked to make directional similarity judgments ("How similar is object A to object B?") for two stationary images drawn from the morph continuum. Across three experiments, similarity ratings for identical comparisons we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Although others have emphasized the role of generative models in visual shape perception3423354163, none of these models distinguishes between geometrically similar parts with different causal origins (e.g., whether a concavity is intrinsic or extrinsic). Moreover, there remains little in the way of experimental work on the visual inference—and use—of generative models of shape for material perception64, category learning656667 and other complex tasks that lie at the intersection between vision and cognition. To what extent such tasks can be solved by simple feedforward pattern recognition architectures or whether they require more sophisticated internal models, including inferences about hidden processes, is a major open question for future research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although others have emphasized the role of generative models in visual shape perception3423354163, none of these models distinguishes between geometrically similar parts with different causal origins (e.g., whether a concavity is intrinsic or extrinsic). Moreover, there remains little in the way of experimental work on the visual inference—and use—of generative models of shape for material perception64, category learning656667 and other complex tasks that lie at the intersection between vision and cognition. To what extent such tasks can be solved by simple feedforward pattern recognition architectures or whether they require more sophisticated internal models, including inferences about hidden processes, is a major open question for future research.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, we did not provide any explicit verbal instructions other than asking observers to identify the front, back, and center of the given shape by placing dots. Each block consisted of 72 trials (four shapes times three transformations times six repetitions)676869.…”
Section: Methodsmentioning
confidence: 99%
“…The project's budget only allowed for the purchase of one set of 24 stimuli. Hahn, et al (2009) showed that perceived similarity judgments for identical morphs were influenced by the directionality of the transformational sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, transformational asymmetries are also in play in a study by Hahn et al This study sought to examine whether an inherent sense of transformation direction may be artificially induced. Participants viewed a short clip showing a continuous morphing transformation between two morph endpoints.…”
Section: Models Of Similaritymentioning
confidence: 99%